Phenomenology of the Reduced Minimal 3-3-1 Model - Lam, Tran Thanh; Thao, Nguyen Chi; Tinh, Ho Hoang; Xinh, Nguyen Thi; Xuyen, Nguyen Van; Long, Hoang Ngoc (Communications in Physics, 2013)
The detailed analysis of the gauge model based on \(SU(3)_CSU(3)_L U(1)_X\) group with minimal content of lepton and Higgs is presented. It is shown that with just two Higgs triplets, all fermions and gauge bosons can get correct masses. The advantage of the model under consideration is that a huge number of free parameters is reduced, and the model’s predictiveness is much improved